A Century Later: Rural Public Health’s Enduring Challenges and Opportunities - Ziller, Erika; Milkowski, Carly (American journal of public health (1971), 2020)
The US public health community has demonstrated increasing awareness of rural health disparities in the past several years. Although current interest is high, the topic is not new, and some of the earliest public health literature includes reports on infectious disease and sanitation in rural places. Continuing through the first third of the 20th century, dozens of articles documented rural disparities in infant and maternal mortality, sanitation and water safety, health care access, and among Black, Indigenous, and People of Color communities. Current rural research reveals similar challenges, and strategies suggested for addressing rural–urban health disparities 100 years ago resonate today. This article examines rural public health literature from a century ago and its connections to contemporary rural health disparities. We describe parallels between current and historical rural public health challenges and discuss how strategies proposed in the early 20th century may inform current policy and practice. As we explore the new frontier of rural public health, it is critical to consider enduring rural challenges and how to ensure that proposed solutions translate into actual health improvements. (Am J Public Health. 2020;110:1678–1686. https://doi.org/10.2105/AJPH.2020.305868 )